2(2x+4)+6=3+3(x-7)

Simple and best practice solution for 2(2x+4)+6=3+3(x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x+4)+6=3+3(x-7) equation:


Simplifying
2(2x + 4) + 6 = 3 + 3(x + -7)

Reorder the terms:
2(4 + 2x) + 6 = 3 + 3(x + -7)
(4 * 2 + 2x * 2) + 6 = 3 + 3(x + -7)
(8 + 4x) + 6 = 3 + 3(x + -7)

Reorder the terms:
8 + 6 + 4x = 3 + 3(x + -7)

Combine like terms: 8 + 6 = 14
14 + 4x = 3 + 3(x + -7)

Reorder the terms:
14 + 4x = 3 + 3(-7 + x)
14 + 4x = 3 + (-7 * 3 + x * 3)
14 + 4x = 3 + (-21 + 3x)

Combine like terms: 3 + -21 = -18
14 + 4x = -18 + 3x

Solving
14 + 4x = -18 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
14 + 4x + -3x = -18 + 3x + -3x

Combine like terms: 4x + -3x = 1x
14 + 1x = -18 + 3x + -3x

Combine like terms: 3x + -3x = 0
14 + 1x = -18 + 0
14 + 1x = -18

Add '-14' to each side of the equation.
14 + -14 + 1x = -18 + -14

Combine like terms: 14 + -14 = 0
0 + 1x = -18 + -14
1x = -18 + -14

Combine like terms: -18 + -14 = -32
1x = -32

Divide each side by '1'.
x = -32

Simplifying
x = -32

See similar equations:

| -3/4u-2/3=-3/4 | | 18n^2-48n-96=0 | | 1/2x-16=32 | | 56v^2+464v+128=0 | | 3(w+4)=-9w-24 | | 3x-4x+3x-6= | | 4x+3=-5x+3 | | x/5-6=10 | | 3(x+4)=2(2x-3) | | -3m-1=-25 | | 6y-1=27+y | | -7x+9x-3x+6-4+13x=18 | | 8k^2+24k-66=0 | | 5x+10y-15=0 | | 12x=36x^2 | | -4-9=-13 | | 6k^2+48k+90=0 | | 4(x+4)+3(x-1)=-15 | | 3(2g+1)-2(g+5)= | | 27x+17=-30 | | eEx=36 | | 15x+21=7x-19 | | x^3+4= | | 64x=24 | | 25x^2+165x+200=0 | | 40a^2+195a+140=0 | | 135-v=223 | | 11e-4e= | | 6x+10=-56-5x | | 226=-y+163 | | 6x+50=13x-8 | | fx=-2/7×2 |

Equations solver categories